Bentuk Implementasi Pendidikan Multikultural Berbasis Kearifan Lokal Pada Makna Gending Seblang Olehsari Banyuwangi - Afifatul Hikmah, Siti Nur (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2024)
The implications of multicultural education are important for changing education and culture throughout society. One of them is through local wisdom as a set of values that are practiced in a society, which are believed to be true both explicitly and implicitly and are used as a guide to behavior in everyday life in a society. Local wisdom is valued as a source of educational innovation based on local community culture. Like the government in providing education. This research aims to determine and analyze the form of implementation of multicultural education based on local wisdom in Gending Seblang Olehsari Banyuwangi. Researchers use qualitative research methods with a type of realist ethnographic research with a cultural studies perspective, namely research that can be said to be able to dig up detailed information from many sources related to a community's culture. The data collection techniques used were observation, field notes, interviews, and documentation studies. The importance of maintaining the inclusive school paradigm is that every student with a different cultural background also gets the right to an education that meets the student's needs. Instilling humanist attitudes and values between ethnic groups with different cultures is built in solidarity and prevents conflict between ethnic groups.